The Illusion of Civil Society : Democratization and Community Mobilization in Low-Income Mexico - Shefner, Jon, 1958- (Book collections on Project MUSE., 2008)
"Addresses the success and failures of the Unión de Colonos Independientes (UCI), a community organization in Guadalajara, Mexico. Critiques the civil society concept and questions the strategy of political democratization as a way to assert control over the global economy"--Provided by publisher.